Impact of Preanalytical and Analytical Methods on Cell-Free DNA Diagnostics - Krasic, Jure; Abramovic, Irena; Vrtaric, Alen; Nikolac Gabaj, Nora; Kralik-Oguic, Sasa; Katusic Bojanac, Ana; Jezek, Davor; Sincic, Nino (Frontiers in Cell and Developmental Biology, 2021)
While tissue biopsy has been the gold-standard in biomedicine, precision/personalized medicine is making the shift towards liquid biopsies. Genetic and epigenetic markers of cell-free DNA (cfDNA) reflect the molecular status of its tissue-of-origin. Preanalytical procedures including cfDNA isolation as well as analytical methods are known to impact the downstream results. Calls for greater standardization are made continuously, yet comprehensive assessments of their impact on diagnostic parameters are lacking. Text mining analysis has been performed to assess cfDNA research trends as well as semen as the source of liquid biopsy. Seminal and blood plasma were tested as liquid biopsy sources. Traditional methods of cfDNA isolation, commercial kits, and an in-house developed protocol were tested, as well as the impact of DTT on cfDNA isolation performance. Fluorimetry, qPCR, ddPCR, and bioanalyzer were compared as cfDNA quantification methods. Fragment analysis was performed by qPCR and Bioanalyzer while the downstream application (cfDNA methylation) was analyzed by pyrosequencing. In comparison to blood, semen as a liquid biopsy source has only begun to be researched, with almost half of all publications on it being review articles. Different protocols gave a wide range of cfDNA yields, both from blood and seminal plasma. The addition of DTT to commercial kits has improved yields in seminal plasma and had a neutral/negative impact in blood plasma. Capillary electrophoresis and fluorometry report much higher yields than PCR methods. While cfDNA yield and integrity were highly impacted, DNA methylation was not affected by isolation methodology or DTT. Nucleosnap was recognized as the kit with the best overall performance. DTT improved commercial kit yields in seminal plasma. The in-house developed protocol has shown near-kit isolation performance. ddPCR LINE-1 assay for absolute detection of minute amounts of cfDNA was established. cfDNA methylation is a stable biomarker irrespective of cfDNA isolation method. Semen as the source of cfDNA offers many potential research opportunities and benefits.